Multiplex PCR followed by restriction length polymorphism analysis for the subtyping of bovine herpesvirus 5 isolates - Maidana, Silvina Soledad (2013)
Background: Several types and subtypes of bovine herpesviruses 1 and 5 (BoHV-1 and BoHV-5) have been associated to different clinical conditions of cattle, making type/subtype differentiation essential to understand the pathogenesis and epidemiology of BoHV infections. BoHV-5 subtyping is currently carried out by BstEII restriction enzyme analysis (REA) of the complete virus genome. This method allowed the description of three subtypes, one of which is the most widespread while the remaining two have so far only been found in South America. The present work describes a multiplex PCR followed by REA for BoHV-5 subtyping. Results: The method consists in the simultaneous amplification of glycoprotein B and UL54 gene fragments of 534 and 669 base pairs (bp), respectively, BstEII digestion of amplicons, separation of products in 1% agarose gels, and analysis of fragment length polymorphims. The multiplex PCR detected up to 227 BoHV-5 genome copies and 9.2 × 105 BoHV-5 genome copies when DNA was extracted from purified virus or infected tissue homogenates, respectively. The applicability of multiplex PCR-REA was demonstrated on 3 BoHV-5 reference strains. In addition, subtyping of two new isolates and seventeen previously reported ones (17 BHV-5a and 2 BHV-5b) by this method gave coincident results with those obtained with the classic BstEII REA assay. Conclusions: Multiplex PCR-REA provides a new tool for the fast and simple diagnosis and subtyping of BoHV-5.